1988
DOI: 10.1007/bf02498790
|View full text |Cite
|
Sign up to set email alerts
|

Manometric evaluation of esophageal motility in patients submitted to prophylactic variceal sclerosis

Abstract: Sclerotherapy of esophageal varices is an effective hemostatic treatment and may also prevent bleeding. In our study, we examined the effects of prophylactic sclerotherapy on esophageal motility in 15 patients with Child's A cirrhosis of the liver. All the patients underwent three manometric measurements, performed respectively before the sclerotherapy, 1 week after the eradication of varices, and 3 months later. The results of our study show that prophylactic sclerotherapy of esophageal varices does not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some authors noticed a decrease in pressure 3,10,13 while others did not show any changes. [5][6][7] Our results showed a significant percentage of patients with hypotonic LES and a positive correlation between the number of sclerotherapy sessions and LES basal pressure. In fact, Sharma et al 13 showed not only the same results but also noticed that the degree of chronic inflammatory cell infiltrate and fibrosis parallels the number of sessions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Some authors noticed a decrease in pressure 3,10,13 while others did not show any changes. [5][6][7] Our results showed a significant percentage of patients with hypotonic LES and a positive correlation between the number of sclerotherapy sessions and LES basal pressure. In fact, Sharma et al 13 showed not only the same results but also noticed that the degree of chronic inflammatory cell infiltrate and fibrosis parallels the number of sessions.…”
Section: Discussionmentioning
confidence: 83%
“…Previous reports focused on the alteration of esophageal motility after endoscopic therapy. [3][4][5][6][7][8][9][10][11][12][13] These studies, however, relied on conventional manometry for the evaluation. High-resolution manometry (HRM) is probably a more adequate tool to measure esophageal motility in these patients.…”
Section: Introductionmentioning
confidence: 99%